An Easy‐to‐Fabricate Hydrogel Platform with Tunable Stiffness and Cell Anchorage: Validation of Its Feasibility in Modulating Sonic Hedgehog Signaling Pathway Physically. Issue 4 (14th April 2020) - Yu, Tingting; Hu, Ke; Xu, Qiufan; Xu, Xueqin; Du, Chunyue; Zhao, Yinyi; Yan, Sen; Wang, Wei; Tang, Shijia; Yue, Shen; Zhang, Xiya; Wang, Danlei; et al.
Abstract : Back Cover : In article number 1900759, Feimin Zhang, Steven Yan Cheng, Ning Gu, and co‐workers develop an IPN hydrogel group with gradient stiffness and cell anchor points, and report that the matrix stiffness and adhesion property functions as key regulators to determine the final output of "Sonic Hedgehog" (Shh) signaling. These results indicate the feasibility of applying this hydrogel platform to low‐cost, high throughput screening of signal pathways which are responsive to the biophysical changes of microenvironments.